Engineering Design Process (EDP) Learning Model on Learning Outcomes, Critical Thinking and Communication Skills of Science Education Students - Mellyatul Aini; Meliyana Aini; Aufa Maulida Fitrianingrum; Zakaria Sandy Pamungkas; Jovialine Albertine Rungkat; Kurniahtunnisa (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Some 21st century skills that must be possessed by students are critical thinking and communication skills. This study aims to determine the effect of using the Engineering Design Process (EDP) learning model on learning outcomes, critical thinking skills and student communication skills. The approach used is the Science, Technology, Engineering, and Mathematics (STEM) approach. The method used in this research is experimental method (one group pretest posttest). The research subjects were undergraduate students of Science Education, Universitas Negeri Manado. The results showed that the average percentage value of N-gain was 59.57% with a fairly effective category. 88.10% of the overall mean score of students' critical thinking skills with excellent category. As much as 82.14% of the average score obtained on student communication skills with excellent category. It can be concluded that the application of EDP learning model with STEM approach can improve learning outcomes, critical thinking skills and student communication. This study contributes to the development of innovative learning by proving that the STEM-based EDP model effectively improves student learning outcomes, critical thinking, and communication. These findings support the integration of 21st-century skills in science education to create more applicable and collaborative learning.